일개 종합병원 간호사의 긍정심리자본, 셀프리더십, 관계유대가 조직몰입에 미치는 영향 - 권시내(Kwon, Shi Nae); 박효정(Park, Hyo Jung) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2020)
본 연구의 목적은 간호사의 긍정심리자본, 셀프리더십, 관계유대와 조직몰입과의 관계 및 조직몰입에 영향을 미치는 요인을 파악하기 위함이다. 자료수집은 2019년 1월 1일부터 3월 31일까지 일개 종합병원에서 근무하는 199명의 간호사를 대상으로 하였다. 자료분석은 SPSS / WIN 23.0 프로그램을 사용하여 분석하였으며, 긍정심리자본의 평균 점수는 3.31±0.44점, 셀프리더십은 3.44±0.40점, 관계유대는 3.54±0.79점, 조직몰입은 3.81±0.76점으로 나타났다. 조직몰입은 긍정심리자본(r=.40, p<.001), 셀프리더십(r=.33, p<.001) 및 관계유대(r=.51, p<.001)와 유의한 상관관계가 나타났다. 단계적 다중회귀 분석에서 간호사의 조직몰입에 영향을 미치는 요인은 긍정심리자본과 관계유대로, 조직 몰입의 29.0 %를 설명하였다. 이상의 결과에서 간호사를 위한 긍정심리자본과 관계유대를 강화하기 위한 효과적인 전략을 수립 할 필요가 있음을 보여줬으며, 이러한 전략은 조직몰입을 향상시킬 수 있을 것이다. Purpose: The purpose of this study was to investigate the association between nurses’ positive psychological capital, self-leadership, relational bonds, and organizational commitment, and to identify factors influencing organizational commitment. Methods: The participants in this study were 199 nurses conveniently selected at one general hospital in Seoul. Data collection was conducted between January 1st and March 31st, 2019, and was analyzed using the SPSS/WIN 23.0 program. Results: The mean score for positive psychological capital was 3.31±0.44, for self-leadership, 3.44±0.40, for relational bonds, 3.54±0.79, and for organizational commitment, 3.81±0.76. Positive psychological capital (r=.40, p<.001), self-leadership (r=.33, p<.001) and relational bonds (r=.51, p<.001) showed significant correlation with organizational commitment. Stepwise multiple regression analysis showed that positive psychological capital and relational bonds were included in the factors affecting the organizational commitment of clinical nurses. These variables explained 29.0% of organizational commitment. Conclusion: Findings indicate that it is necessary to build effective strategies to enhance positive psychological capital and relational bonds for nurses. Such strategies will result in improved organizational commitment. KCI Citation Count: 0